(3MhGTj YHOGddWja GdHZOGOj Ydi GdbGfhfs - (3ehab GdOjf YHO GddWja Hf jhSa GdHZOGOjs; (3GdQFjS GHf SjfG , CHh Ydj TQa Gdedc (B: (3GdajdSha GdQFjS,J (B428 (3g` s
(3ChdgG (B:s
(3Efg dGjYQa eTGb GdCYeGd EdG ef cGf dg eTGQcI ajgG heRGhdI dgG ceG bGd dGjYQa GdThb EdG ef oecGHOI hdG GdUHGHI EdG ef ojYGfjgG hEPG CQGO GdeQA GdYGbd Cf jYde TQa GdCeQ GdeUfhY Ch ebOGQ GdJYH ajg s
(3BNQgG (B:s
(3hbOSHb PcQgG ai GdeYGLjf hChRGfgG ZjQ ChRGfgG EdG Cf GdfSHI hGMOI hGdOhGA hGMO BNQ eGocJH Ydi GdbGfhf s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQI GdYfhGf (B:s
(3JPjjds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
Keywords: (3GdWHs